Challenges for HCV vaccine development in HIV–HCV coinfection. (July 2012) - Lambotin, Mélanie; Barth, Heidi; Moog, Christiane; Habersetzer, François; Baumert, Thomas F; Stoll-Keller, Françoise; Fafi-Kremer, Samira
It is estimated that 4–5 million HIV-infected patients are coinfected with HCV. The impact of HIV on the natural course of HCV infection is deleterious. This includes a higher rate of HCV persistence and a faster rate of fibrosis progression. Coinfected patients show poor treatment outcome following standard HCV therapy. Although direct antiviral agents offer new therapeutic options, their use is hindered by potential drug interactions and toxicity in HIV-infected patients under HAART. Overtime, a large reservoir of HCV genotype 1 patients will accumulate in resource poor countries where the hepatitis C treatment is not easily affordable and HIV therapy remains the primary health issue for coinfected individuals. HCV vaccines represent a promising strategy as an adjunct or alternative to current HCV therapy. Here, the authors review the pathogenesis of hepatitis C in HIV-infected patients, with a focus on the impact of HIV on HCV-specific immune responses and discuss the challenges for vaccine development in HIV–HCV coinfection.